Infectious Complications in Kidney-Transplant Recipients Desensitized with Rituximab and Intravenous Immunoglobulin - Kahwaji, Joseph (American Society of Nephrology, 2011)
SUMMARY: BACKGROUND AND OBJECTIVES: Rituximab and intravenous Ig (IVIG) are commonly used for desensitization of HLA and blood group–incompatible (ABOi) transplants. However, serious infections have been noted in association with rituximab administration. In this study, we retrospectively compared infectious outcomes in those who received rituximab plus IVIG for HLA or ABOi transplants (RIT group) with a group of nonsensitized, ABO-compatible transplant recipients (non-RIT group). DESIGN, SETTING, PARTICIPANTS, & MEASUREMENTS: Patients undergoing kidney transplantation at Cedars-Sinai Medical Center were included in the analysis. A total of 361 patients were identified. All received antimicrobial prophylaxis and viral surveillance. The primary outcome was infection. RESULTS: Overall patient survival was 97 and 96%, and graft survival was 91 and 89% in the RIT and non-RIT groups, respectively, after an average follow-up of 18 months. There were equal rates of bacterial (34.7% versus 39.1%), viral (21.8% versus 25.1%), fungal (5.9% versus 5.2%), and serious infections (22.9% versus 25.5%) in the RIT and non-RIT groups respectively. Urinary tract infection was the most common infection, accounting for 50% of all bacterial infections. Cytomegalovirus viremia was nonsignificantly more common in the nonrituximab-treated group (15.2% versus 10%), whereas BK viremia was marginally more frequent in the rituximab-treated group (10.6% versus 5.8%). There were no graft losses caused by BK-associated nephropathy. There were two deaths in each group related to infection (1%). CONCLUSION: Rituximab does not increase infection risk when used with intravenous Ig for desensitization.